1976
DOI: 10.1007/bf02486557
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low extracellular pH upon the Ca inward current and isometric contractile force in mammalian ventricular myocardium

Abstract: In isolated papillary muscles of cats the changes in Ca inward current and isometric contractile force following a decrease of extracellular pH from 7.4 to 5.5 were studied. The Ca current was analyzed (a) by measuring the upstroke velocity of Ca-mediated action potentials and (b) in voltage clamp experiments using the double sucrose gap technique. 1. At a pH of 5.5 the upstroke velocity of the Ca-mediated action potential decreased to 65% of the control, while overshoot and action potential duration remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

1982
1982
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 29 publications
(25 reference statements)
4
33
0
1
Order By: Relevance
“…In the frog atrial muscle, low pH decreases both IS and the outward current (CHESNAIS et al, 1975;WADA and GoTo, 1975). Our results are similar to those of KoHLHARDT et al (1976), however they found no shift of the I-V curve when the external pH was changed from 7.4 to 5.5, while in our experiments, I -V curve shifted to a less negative voltage. A genuine species difference, or unknown differences in experimental technique may be involved in the discrepancy.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the frog atrial muscle, low pH decreases both IS and the outward current (CHESNAIS et al, 1975;WADA and GoTo, 1975). Our results are similar to those of KoHLHARDT et al (1976), however they found no shift of the I-V curve when the external pH was changed from 7.4 to 5.5, while in our experiments, I -V curve shifted to a less negative voltage. A genuine species difference, or unknown differences in experimental technique may be involved in the discrepancy.…”
Section: Discussionsupporting
confidence: 88%
“…With respect to earlier observations in the cat papillary muscle, it has been reported that reduction of external pH reduces the slow inward current and increases the time constant of inactivation (KoHLHARDT et al, 1976). In the frog atrial muscle, low pH decreases both IS and the outward current (CHESNAIS et al, 1975;WADA and GoTo, 1975).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Perivascular pH can affect many cellular processes (4), but the precise mechanisms of vascular hyporesponsiveness remain uncertain. Low pH has been shown to reduce Ca 2+ influx (37), to inhibit myofilament contractility (38) and to alter receptors on the cell surface (39), accounting for the attenuation of vasoconstrictor responses.…”
Section: Metabolic Acidosismentioning
confidence: 99%
“…One such perturbation is extracellular acidosis, which can occur during myocardial ischemia. Chesnais et al (1975), Kohlhardt et al (1976), and Yatani and Goto (1983) have all shown that acidosis depresses Ca channel current and, therefore, overall cardiac performance.…”
Section: Introductionmentioning
confidence: 99%